Investigation of the effect of biogas on combustion and emissions of TBC diesel engine - YILMAZ, İLKER TURGUT (ELSEVIER SCI LTD, 2017)
In this study, the effect of biogas on the thermal barrier coated (TBC) dual-fuel engine was experimentally investigated. Experiments were carried out on a four cylinder, water cooled, turbocharged, common-rail coated and uncoated diesel engine under dual-fuel (biogas-diesel) mode and single fuel (neat diesel) mode. Combustion chambers of the pistons were coated with 400 mu m thickness 8% yttria stabilized zirconia main coat over a 100 mu m thickness Ni-Al bond coat using atmospheric plasma spray method. Combustion (cylinder gas pressure, rate of pressure rise), heat release (rate of heat release, cumulative heat release, duration and center of heat release) exhaust emission (HC, NOx and smoke emissions) parameters were investigated. Results showed that homogenous mixture of gaseous fuel and air caused high cylinder pressures. TBC can be used for decreasing smoke emissions under dual-fuel (biogas-diesel) mode. TBC had not a significant effect on NOx emission of single fuel mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Biogas; Dual-fuel diesel engine; Combustion; Heat release; SPARK-IGNITION ENGINE; DUAL FUEL MODE; PRODUCER GAS; NATURAL-GAS; PERFORMANCE-CHARACTERISTICS; METHYL-ESTER; SIMULATED BIOGAS; COIR-PITH; HYDROGEN; INJECTION